AN EXPLORATORY ANALYSIS OF FINANCIAL INCLUSION IN CHAD - AHMAT TIDJANI, Mahamat Ibrahim (The European Journal of Applied Economics, 2020)
This paper aimed to explore the state of financial inclusion in Chad. Using demand-side data, the Global Findex (2017), the study measured through a Financial Inclusion Index (FII) the inclusiveness of financial systems in Chad adopting a Multiple Correspondence Analysis (MCA). Further, it assessed the distribution of the FII using the factor decomposition of the Gini coefficient. The findings showed that the average FII was low, 24.89%, and it varied between 7.43% and 60.35%. The financial institution account ownership, withdrawal, deposit, and debit card were the most important dimensions of financial inclusion. Further, the paper revealed that despite its low level, access to and use of formal financial services was not smoothly distributed among the Chadian population (Gini coefficient of 0.196). The analysis of the financial inclusion inequality profile showed that there was a persistent financial inclusion gender gap in access to formal financial services in Chad, exacerbated by discriminations in education and income. Thus, building the profile of the specific target in each group will help policymakers to formulate adequate policy interventions to enhance financial inclusion in Chad. The government should formulate gender-responsive policies to expand financial inclusion.